Short- and long-term exposure to ambient air pollution and greenness in relation to pulmonary tuberculosis incidence - Dongmiao Yuan; Bo Xie; Zhe Pang; Kui Liu; Bin Chen (Scientific Reports)
Abstract Epidemiological studies have found inconsistent relationships between air pollutants and the risk of pulmonary tuberculosis (PTB), possibly due to variations in exposure windows and limited attention to environmental modifiers such as greenness. However, few studies has systematically examined how short- and long-term exposure to air pollution may differentially impact PTB risk, and how greenness may modify these associations. We utilized comprehensive data, including daily PTB incidence, air pollutants, meteorological data, and the normalized difference vegetation index (NDVI) from Zhejiang Province, China, spanning from 2013 to 2019. A distributed lag nonlinear model (DLNM) was employed to examine the relationships between air pollution and PTB incidence by county, and a meta-analysis was conducted to aggregate county-specific estimates. In the single-pollutant model, the lag-specific excess risk (ER) of PTB was 0.7% (95% CI 0.05%, 1.4%, 13-week lag) for each 0.1 mg/m3 increase in carbon monoxide (CO). For each 10 µg/m3 increase in the combined oxidant capacity (OX), the lowest risk was a 0.9% decrease (95% CI −1.5%, −0.3%, 16-week lag). For each 10 µg/m3 increase in particulate matter 2.5 (PM2.5), the highest risk was a 1.7% increase (95% CI 0.8%, 2.6%, 19-week lag). Conversely, each 10 µg/m3 increase in sulfur dioxide (SO2) showed a dual association with PTB incidence, encompassing a short-term negative correlation and a long-term positive correlation. Furthermore, the associations between CO and PM2.5 and PTB incidence were more pronounced in the male and working-age subgroups, whereas the associations with SO2 were more significant in the female and elderly subgroups. Additionally, we observed that greenness negatively modified the relationship between short- and long-term exposure to OX and PTB incidence. Our findings revealed significant long-term lagged effects of CO, OX, and PM2.5 on PTB incidence, as well as short- and long-term lagged effects of SO2. Furthermore, greenness was identified as a modifier of the association between OX and PTB incidence at various lag times.